(Super)gelators derived from push–pull chromophores: synthesis, gelling properties and second harmonic generation. Issue 14 (21st March 2018) - Belén Marco, A.; Gindre, Denis; Iliopoulos, Konstantinos; Franco, Santiago; Andreu, Raquel; Canevet, David; Sallé, Marc
Abstract : New organogelators including push–pull chromophores are described and show that second harmonic generation active materials can be prepared without sophisticated processes. Abstract : The present work takes advantage of the self-assembly process occurring along organogelation, to organize Second Harmonic Generation (SHG) active chromophores. To do so, three push–pull chromophores endowed with a dodecyl urea chain were synthesized and characterized. Their organogelating properties were studied in a wide range of solvents. Despite similar architectures, these derivatives exhibit very different gelling properties, from supergelation to the absence of gelling ability. The utilization of the Hansen solubility parameters allows for observing clear relationships between the gelled solvents and critical gelation concentrations. By evaporating the solvents from the organogels, xerogel materials were prepared and systematically studied by means of optical and electron microscopy as well as SHG microscopy. These studies demonstrate the critical role of the solvent over material structuring and allow generalizing the approach exploiting organogelation as a structuring tool to spontaneously organize push–pull chromophores into SHG-active materials.